Diagnosing the Downstream Impact of Extratropical Transition Using Multimodel Operational Ensemble Prediction Systems - Keller, Julia Henriette (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2013)
The study examines the predictability during the extratropical transition (ET) of tropical cyclones using the THORPEX Interactive Grand Global Ensemble (TIGGE), a multimodel ensemble prediction system (EPS). It is shown that TIGGE exhibits more possible development scenarios than a single EPS. By analysing the eddy kinetic energy budget of forecast scenarios for two ET cases, extracted from an EPS, the impact of the transitioning tropical cyclones on the midlatitude flow is studied in detail.